Komunikasi Suportif Pelatih Kepada Atlet Taekwondo BGFC Pasca Kekalahan Di Kejuaraan - Shalihah, Mutia Rieza; Fitriawati, Diny (KOMUNIKA BANGSA, 2025)
Defeat in a championship is a major challenge for athletes, not only physically but also emotionally, which can potentially lower self-confidence, motivation, and even the desire to continue training. This study aims to understand how coaches support BGFC Taekwondo athletes after losing in a championship. The main focus of this study includes the emotional, informational, and instructional support provided by coaches to help athletes recover from failure. This study employs a qualitative method with a descriptive approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation involving one coach and three athletes at the BGFC Taekwondo unit. The results indicate that supportive communication, both verbal and non-verbal, plays a crucial role in rebuilding athletes' self-confidence and accelerating mental recovery after a loss. Coaches who provide empathetic support, constructive feedback, and clear technical guidance are able to create positive interpersonal relationships, thereby encouraging athletes' motivation and readiness to train again and achieve success in the future. This study makes an important contribution to enriching the literature on sports communication and can serve as a practical reference for coaches in creating effective and supportive communication patterns